TEACHING ARUDH WAL QAWAFI USING MADRASA PLATFORM: A CASE STUDY AT SYAMSUL ULUM MUHAMMADIYAH ISLAMIC BOARDING SCHOOL BANDUNG / PLATFORM MADRASA UNTUK PENGAJARAN ARUDH WAL QAWAFI: STUDI KASUS DI PONDOK PESANTREN SYAMSUL ULUM MUHAMMADIYAH BANDUNG - Muhammad Ibnu Pamungkas (IAIN Batusangkar, Indonesia, 2023)
This study aims to explore the teaching process of arudh wal qawafi, the use of Madrasa platform as an instructional media, and students’ response toward the use of the platform at Syamsul Ulum Muhammadiyah Islamic boarding school, Bandung. This research employed a descriptive qualitative approach using a case study method. The subjects were the twelve grade students of Syamsul Ulum Muhammadiyah Islamic Boarding School Bandung in 2022-2023 academic year. Based on the findings, arudh wal qawafi has been taught in grade XII at the Syamsul Ulum Muhammadiyah Bandung Islamic Boarding School since 2021 since it is seen as an important subject for students. Arudh wal qawafi is taught in stages applying teacher-made modules. At the reinforcement stage of the subject, the Madrasa platform is used as an instructional media. Students responded positively to the use of Madrasa platform in learning arudh wal qawafi since it may help them understand the subject matter. Students as Madrasa platform users are satisfied to the level of 83.5%.